Covert Infection of Insects by Baculoviruses - Williams, Trevor; Virto, Cristina; Murillo, Rosa; Caballero, Primitivo (Frontiers in Microbiology, 2017)
Baculoviruses (Baculoviridae) are occluded DNA viruses that are lethal pathogens of the larval stages of some lepidopterans, mosquitoes and sawflies (phytophagous Hymenoptera). These viruses have been developed as biological insecticides for control of insect pests and as expression vectors in biotechnological applications. Natural and laboratory populations frequently harbor covert infections by baculoviruses, often at a prevalence exceeding 50%. Covert infection can comprise either non-productive latency or sublethal infection involving low level production of virus progeny. Latency in cell culture systems involves the expression of a small subset of viral genes. In contrast, covert infection in lepidopterans is associated with differential infection of cell types, modulation of virus gene expression and avoidance of immune system clearance. The molecular basis for covert infection may reside in the regulation of host-virus interactions through the action of microRNAs (miRNA). Initial findings suggest that insect nudiviruses and vertebrate herpesviruses may provide useful analogous models for exploring the mechanisms of covert infection by baculoviruses. These pathogens adopt mixed-mode transmission strategies that depend on the relative fitness gains that accrue through vertical and horizontal transmission. This facilitates virus persistence when opportunities for horizontal transmission are limited and ensures virus dispersal in migratory host species. However, when host survival is threatened by environmental or physiological stressors, latent or persistent infections can be activated to produce lethal disease, followed by horizontal transmission. Covert infection has also been implicated in population level effects on host-pathogen dynamics due to the reduced reproductive capacity of infected females. We conclude that covert infections provide many opportunities to examine the complexity of insect-virus pathosystems at the organismal level and to explore the evolutionary and ecological relationships of these pathogens with major crop and forest pests.